Complete mitochondrial genome of squaretail coralgrouper Plectropomus areolatus (Perciformes, Epinephelidae). (August 2013) - Shen, Minghui; Shi, Xiaofeng; Qu, Meng; Chen, Jun
<x xml:space="preserve">Abstract</x> The complete mitochondrial genome (mitogenome) sequence of squaretail coralgrouper Plectropomus areolatus was determined with long PCR approach. The genome was 16, 770 bp in length and contained 13 protein-coding genes, 22 transfer RNAs (tRNAs), 2 ribosomal RNAs (rRNAs), and 2 non-coding regions, with the gene content and order being similar to most other teleosts. The overall base composition of the mitogenome was estimated to be 28.81% A, 27.63% T, 27.24% C, and 16.33% G, with a high AT content of 56.44%, indicating an obvious anti-guanine bias commonly observed in fishes. It shared 90.7%, 78.8%, and 78.7% mitogenome sequence with Plectropomus leopardus, Epinephelus moara, and Epinephelus coioides, respectively.